Reproductive strategy of Coptotermes gestroi (Isoptera: Rhinotermitidae) in Brazil - Costa-Leonardo, Ana Maria [UNESP]; Arab, Alberto [UNESP] (My University, 2004)
The termite Coptotermes gestroi (Wasmann) (Rhinotermitidae) is an exotic species in Brazil. This species forms colonies headed by primary reproductives, however, non-functional neotenics are commonly found even in the presence of the imaginai pair. The presence of non-functional neotenics in C. gestroi colonies may correspond to a strategy of this termite species for rapid colonization in foreign areas, instead of a response to chemical control methods.
Keywords: Neotenics; Nymphs; Primary reproductives; Replacement reproductives; Subterranean termites; Arthropoda; Coptotermes; Coptotermes gestroi; Invertebrata; Isoptera; Rhinotermitidae